Coordination of vasomotor responses by the endothelium. - Dora, K (2010)
Increases in the diameter of small resistance arteries and arterioles occur secondary to processes that can be dependent or independent of changes in membrane potential. Hyperpolarization reduces the opening of voltage-gated calcium channels and thereby the stimulus for contraction of these resistance vessels. The stimulus for smooth muscle cell (SMC) hyperpolarization can occur directly via opening K(+)-channels expressed within those cells, but can also occur in response to stimulation of endothelial cells (ECs). This endothelium-dependent hyperpolarization (EDH) of smooth muscle often occurs in response to agonists that stimulate a rise in the Ca(2+) concentration of ECs, which in turn can open Ca(2+)-activated K-channels to hyperpolarize the ECs, and if present, patent gap junctions connecting ECs to SMCs (myoendothelial gap junctions) can potentially enable direct electrical coupling. There is also evidence to suggest a diffusible factor or factors hyperpolarizes SMCs (EDHF pathways). Furthermore, whether evoked in ECs or SMCs, hyperpolarization can spread a considerable distance to neighboring cells via gap junctions, causing remote dilatation termed ;spreading' or ;conducted' dilatation. This process is endothelium-dependent and likely relies on both homo- and heterocellular gap junctions. This review will focus on the cross-talk between ECs and SMCs that coordinates the spread of hyperpolarization and thus modulates smooth muscle tone.